2016
DOI: 10.1007/s10597-016-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Social Support Among Chinese Immigrant Mental Health Consumers with Psychosis

Abstract: Limited research has investigated how culture impacts expressions of social support, which is crucial in developing culturally sensitive care. Using a classification based on theories of social support, we examined the social support experiences of 49 Chinese immigrant mental health consumers with psychosis, paying particular attention to frequency and sources. We found that the most common forms of social support were belonging and companionship, perceived emotional support, social control, and perceived inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The availability and sources of social support are especially important for racial/ethnic minorities given previous evidence suggesting that their social networks tend to be smaller than those of non-Hispanic Whites ( McPherson et al, 2006 ; Park et al, 2015 ), and also more reliant on family ( Park et al, 2015 ). Family relationships may be particularly central to social relationships and feelings of belonging among Asian Americans because of traditions of familial obligation and duty ( Zhang and Ta, 2009 ) as well as the threat of ‘losing face’ from sharing personal problems in less intimate social networks ( Cheng et al, 2016 ). Findings among Asian participants in the National Latino and Asian American Study also suggest the primacy of family support in reducing psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…The availability and sources of social support are especially important for racial/ethnic minorities given previous evidence suggesting that their social networks tend to be smaller than those of non-Hispanic Whites ( McPherson et al, 2006 ; Park et al, 2015 ), and also more reliant on family ( Park et al, 2015 ). Family relationships may be particularly central to social relationships and feelings of belonging among Asian Americans because of traditions of familial obligation and duty ( Zhang and Ta, 2009 ) as well as the threat of ‘losing face’ from sharing personal problems in less intimate social networks ( Cheng et al, 2016 ). Findings among Asian participants in the National Latino and Asian American Study also suggest the primacy of family support in reducing psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…A study among Chinese immigrants showed that family and friend support, medical service support, and local government support were the main sources of support for immigrants. These objective support systems benefitted the mental health and physical health of the immigrants, especially those with certain diseases [ 50 ]. Objective support was a main factor that influenced the mental health of immigrants with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few studies focusing on the mental health of immigrants in China. However, there is evidence that relocation-related stressors can affect the mental health of immigrants [ 50 ]. The social factors of immigration and relocation only worsen the mental health of immigrants with chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In China, mental illness is often considered the result of a faulty personality, moral defects, bad genetics, or punishment for misconduct (Li et al, 2014). Because of this, Chinese people living abroad are often difficult to reach and recruit into mental health services (Cheng, Tu, & Yang, 2016; Kim, Zhang, Hou, & Shen, 2020; Ma, Zhu, & Bresnahan, 2021; Yang, Rodgers, Lee, & Lê Cook, 2019). This is problematic as the prevalence of mental illness in Chinese immigrant communities is elevated.…”
mentioning
confidence: 99%
“…Unfortunately, anticipated stigma often leads people with mental health difficulties and their families to conceal mental health difficulties in order to avoid social conflict or community rejection (Yang & Kleinman, 2008; Yin et al, 2014). Evidently, this is a barrier to help seeking (Cheng et al, 2016; J.‐Y. Li, 2021), which in light of the COVID‐19 pandemic, where mental health concerns abound (Wu et al, 2021; Xiong et al, 2020), is particularly problematic.…”
mentioning
confidence: 99%